Kuasa Disiplin dalam Kepemimpinan Perpustakaan Perguruan Tinggi - Annisa Nur Fatwa; L. Nurdin (Pustakaloka, 2021)
A leader is someone who has influence in an organization. One of them is a library that has a leader to achieve its goals. The library of Islamic University of Indonesia is one of the higher education libraries located in the Special Region of Yogyakarta, which is led by a director with an educational background in library science. This study was aimed at investigating disciplinary power  exercised by a director. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation. Data analysis was performed using three stages of analysis based on Miles and Huberman. In its analysis, Michel Foucault's theory of disciplinary power was used as an effort to look at five things, i.e. panopticism, separation of places, documentation, standardization of judgments, and rewards. The results show that the form of power was hierarchical supervision embodied in verbal rules regarding working time, non-verbal staff jobdesk, separation between the library director's room and division, forms of tardiness and absence, work standards and verbal rewards,  and written warnings. Key Words: Discipline Power, Library Leadership, Panopticism, Islamic Libraries, UII Library